Deep brain stimulation in the ventrolateral thalamus/subthalamic area in dystonia with head tremor. Issue 7 (21st April 2014) - Pauls, K. Amande M.; Hammesfahr, Sven; Moro, Elena; Moore, A. Peter; Binder, Ellen; El Majdoub, Faycal; Fink, Gereon R.; Sturm, Volker; Krauss, Joachim K.; Maarouf, Mohammad; Timmermann, Lars
ABSTRACT Background Pallidal deep brain stimulation (GPi‐DBS) effectively ameliorates idiopathic dystonia, although approximately 15% of patients respond insufficiently. Although various thalamic and subthalamic targets have been suggested for dystonic tremor, no systematic studies have been published on thalamic DBS in dystonic tremor. We assessed the effect of thalamic/subthalamic area DBS (Th‐DBS) on dystonic head tremor and dystonia in a single‐blind design. Methods Dystonic head tremor and dystonia before and 3 months after surgery were quantified via blinded video‐ratings using the Fahn‐Tolosa‐Marin‐Tremor‐Scale and the Burke‐Fahn‐Marsden‐Dystonia‐Rating‐Scale in seven patients with idiopathic cervical or segmental dystonia, dystonic head tremor, and bilateral Th‐DBS. Pain, side effects, adverse events, and stimulation parameters were assessed. Results Th‐DBS improved dystonic tremor and dystonia (P < 0.05; 57.1% and 70.4%, respectively). Head tremor amplitude and pain were also improved (P < 0.05; 77.5% and 90.0%, respectively). Side effects included dysarthria, gait disturbance, slowness of movement, and weight gain. Conclusion Dystonic head tremor and dystonia can be improved with Th‐DBS. © 2014 International Parkinson and Movement Disorder Society